Peroxisome proliferator-activated receptors (PPARs) and ovarian function - implications for regulating steroidogenesis, differentiation, and tissue remodeling - Komar Carolyn M (BMC, 2005)
Abstract The peroxisome proliferator-activated receptors (PPARs) are a family of transcription factors involved in varied and diverse processes such as steroidogenesis, angiogenesis, tissue remodeling, cell cycle, apoptosis, and lipid metabolism. These processes are critical for normal ovarian function, and all three PPAR family members - alpha, delta, and gamma, are expressed in the ovary. Most notably, the expression of PPARgamma is limited primarily to granulosa cells in developing follicles, and is regulated by luteinizing hormone (LH). Although much has been learned about the PPARs since their initial discovery, very little is known regarding their function in ovarian tissue. This review highlights what is known about the roles of PPARs in ovarian cells, and discusses potential mechanisms by which PPARs could influence ovarian function. Because PPARs are activated by drugs currently in clinical use (fibrates and thiazolidinediones), it is important to understand their role in the ovary, and how manipulation of their activity may impact ovarian physiology as well as ovarian pathology.